Spatializing stigma-power: Mental health impacts of spatial stigma in a legally-excluded settlement in Mumbai, India. - Saloni Dev; Jasper Duval; Amith Galivanche; Tejal Shitole; Kiran Sawant; Shrutika Shitole; Anita Patil-Deshmukh; Alisa Lincoln; Ramnath Subbaraman; Liza Weinstein (Public Library of Science (PLoS), 2023)
In disadvantaged neighborhoods such as informal settlements (or "slums" in the Indian context), infrastructural deficits and social conditions have been associated with residents' poor mental health. Within social determinants of health framework, spatial stigma, or negative portrayal and stereotyping of particular neighborhoods, has been identified as a contributor to health deficits, but remains under-examined in public health research and may adversely impact the mental health of slum residents through pathways including disinvestment in infrastructure, internalization, weakened community relations, and discrimination. Based on analyses of individual interviews (n = 40) and focus groups (n = 6) in Kaula Bandar (KB), an informal settlement in Mumbai with a previously described high rate of probable common mental disorders (CMD), this study investigates the association between spatial stigma and mental health. The findings suggest that KB's high rate of CMDs stems, in part, from residents' internalization of spatial stigma, which negatively impacts their self-perceptions and community relations. Employing the concept of stigma-power, this study also reveals that spatial stigma in KB is produced through willful government neglect and disinvestment, including the denial of basic services (e.g., water and sanitation infrastructure, solid waste removal). These findings expand the scope of stigma-power from an individual-level to a community-level process by revealing its enactment through the actions (and inactions) of bureaucratic agencies. This study provides empirical evidence for the mental health impacts of spatial stigma and contributes to understanding a key symbolic pathway by which living in a disadvantaged neighborhood may adversely affect health.